CLOSED-CHAMBER REPAIR OF TRAUMATIC IRIDODIALYSIS UNDER LOCAL ANESTHESIA IN A PHAKIC PEDIATRIC EYE: A CASE REPORT - Ade John Nursalim (Ikatan Dosen Menulis, 2026)
Traumatic iridodialysis is a visually significant form of iris root injury after blunt ocular trauma and may cause photophobia, monocular diplopia, pupillary distortion, polycoria, and reduced visual acuity. Surgical repair in a phakic pediatric eye is technically demanding because the surgeon must restore iris anatomy while preserving the crystalline lens and maintaining a stable anterior chamber. We report the case of a 12-year-old boy who presented with redness, reduced vision, photophobia, monocular diplopia, and pupillary deformity in the right eye two weeks after blunt trauma caused by impact against a water container. Preoperative uncorrected and best-corrected visual acuity were both 6/40, and intraocular pressure was 12 mmHg using iCare tonometry. Examination revealed inferior traumatic iridodialysis extending from 5 to 7 o’clock, involving approximately two clock hours or 60 degrees of the iris circumference. The crystalline lens was clear without subluxation, the fundus was normal, and B-scan ultrasonography showed no posterior segment pathology. The patient underwent closed-chamber iridodialysis repair under local anesthesia using a 27-gauge needle-assisted modified sewing-machine style technique with two Mani 10-0 polypropylene straight sutures. Anterior chamber stability was maintained using a dispersive-cohesive ophthalmic viscosurgical device clam-shell technique. On postoperative day one, documented visual acuity improved to 6/21, although transient intraocular pressure elevation to 32 mmHg occurred and was managed medically with topical brinzolamide. At one-month follow-up, best-corrected visual acuity improved to 6/6, intraocular pressure was 12 mmHg, the pupil remained centered, the crystalline lens was clear, and photophobia and monocular diplopia had resolved. This case supports the short-term feasibility of closed-chamber repair under local anesthesia in carefully selected cooperative older pediatric patients, while emphasizing the need for longer follow-up to monitor delayed angle-related glaucoma, lens clarity, and suture stability.